Activation and Deactivation of DNAzyme and Antisense Function with Light for the Photochemical Regulation of Gene Expression in Mammalian Cells - Young, Douglas D. (2010)
The photochemical regulation of biological systems represents a very precise means of achieving high-resolution control over gene expression in both a spatial and a temporal fashion. DNAzymes are enzymatically active deoxyoligonucleotides that enable the site-specific cleavage of RNA, and have been used in a variety of in vitro applications. We have previously reported the photochemical activation of DNAzymes and antisense agents through the preparation of a caged DNA phosphoramidite and its site-specific incorporation into oligonucleotides. The presence of the caging group disrupts either DNA:RNA hybridization or catalytic activity, until removed via a brief irradiation with UV light. Here, we are expanding this concept by investigating the photochemical deactivation of DNAzymes and antisense agents. Moreover, we report the application of light-activated and light-deactivated antisense agents to the regulation of gene function in mammalian cells. This represents the first example of gene silencing antisense agents that can be turned on and turned off in mammalian tissue culture.